Analisis Pelaksanaan Praktikum Biologi Dan Permasalahannya Di SMAS Muhammadiyah 9 Kualuh Hulu - Fitriyani Fitriyani; Syarifah Widya Ulfa; Miza Nina Adlini (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research aims to analyze and determine the implementation of biology practicum and analyze the problems at SMAS Muhammadiyah 9 Kualuh Hulu. This research was conducted in a laboratory room at SMAS Muhammadiyah 9 Kualuh Hulu. This research is a type of qualitative research in this research which produces descriptive data in the form of written or spoken words from the behavior of the people being observed. Participants in this research were students in classes X, XI, XII IPA. This research uses research procedures in the form of observation, interviews, documentation, questionnaires. The instruments in this research were interview sheets and questionnaire sheets. Data analysis techniques, data reduction (data reduction), data display (data presentation), Conclusion Drawing or Verification (Conclusion or verification). Data validity test, namely triangulation.